Synthesis And Development Of Image Coding Algorithms Based On 2D Descrete Wavelet Transform - Yok Wooi, Matthew Teow (2009)
In this thesis, two wavelet image-coding techniques will be presented. They are the wavelet sub-band energy feature remapping (EFRM) and the wavelet maxima mapping quantisation (WMMQ) algorithms. The EFRM algorithm is a pre-processing techniques for an adaptive arithmetic entropy codec. The objective of the EFRM algorithm is to remap the energy features of the wavelet image sub-bands into a coherence data structure that reduces the sub-band orientation sensitivity.